Literature Review: Kepatuhan Perawat Dalam Penggunaan Alat Pelindung Diri (APD) - Dea Ananda Br.SK; Nur Asiyah Siregar; Sri Hajijah Purba (Journal of Educational Innovation and Public Health, 2024)
Hospitals are vital health facilities that aim to improve public health by providing high-quality health services. This study aims to evaluate nurses' compliance in using Personal Protective Equipment (PPE) in hospitals as an effort to prevent nosocomial infections. Through a literature review of various studies between 2021-2024, it was found that nurse compliance was influenced by knowledge, attitudes and availability of PPE. Good knowledge and positive attitudes towards PPE, as well as adequate accessibility of PPE, have been proven to increase nurse compliance. In addition, demographic characteristics such as age, gender, education, and years of service also influence compliance levels. In conclusion, improving compliance requires a multifactorial approach that includes continuing education, adequate facilities, and close supervision. Implementation of this strategy is important to prevent nosocomial infections and improve the quality of health services in hospitals.